2006
DOI: 10.1016/j.ymthe.2005.09.004
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Genetic Selection of Renal Proximal Tubules

Abstract: Repopulation by transplanted cells can result in effective therapy for several regenerative organs including blood, liver, and skin. In contrast, cell therapies for renal diseases are not currently available. Here we developed an animal model in which cells genetically resistant to a toxic intermediate of tyrosine metabolism, homogentisic acid (HGA), were able to repopulate the damaged proximal tubule epithelium of mice with fumarylacetoacetate hydrolase (Fah) deficiency. HGA resistance was achieved by two ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 46 publications
1
51
0
Order By: Relevance
“…28 Genetic instability, drug withdrawal, chronic injury, inflammation, and ongoing regeneration may play important roles in enhancing BMC engraftment, conversion, and cell fusion in this mouse model.…”
Section: Hgdmentioning
confidence: 94%
See 1 more Smart Citation
“…28 Genetic instability, drug withdrawal, chronic injury, inflammation, and ongoing regeneration may play important roles in enhancing BMC engraftment, conversion, and cell fusion in this mouse model.…”
Section: Hgdmentioning
confidence: 94%
“…These results indicate that proximal tubules are repopulated by fusion of donor BMC with host renal epithelial cells. 28 However, it is not known whether fusion of BMC with renal cells occurs after AKI. We used cre/loxP recombination and sex-mismatched transplantation to examine fusion events in mice after renal IRI.…”
mentioning
confidence: 99%
“…Lin et al [21] and Duffield et al [22] finally concluded that the contribution of bone marrow-derived cells to the kidney was relatively low (0.06-8%). Futhermore, Held et al [23] have shown that a 20-50% cell fusion could be induced between bone marrow-derived cells and renal tubular cells under conditions of chronic renal damage. Nevertheless, BM transplantation can improve renal function.…”
Section: Bone Marrow-derived Cellsmentioning
confidence: 99%
“…Several studies have demonstrated the capacity of MSC to differentiate into kidney cells [11][12][13][14]. Controversial studies indicated that the grafted MSCs were not the predominant cellular components involved in the regeneration of injured tubuli [7,59], and it has been postulated that, rather than differentiation, cell fusion accounts for these cells [7,[59][60][61]. Recent studies have ascribed reparative effects of MSCs to their endocrine/paracrine functions [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%